A universal basic income for Ireland: Lessons from the international literature - Paul Redmond; Séamus McGuinness; Klavs Ciprikis (The Economic and Social Research Institute (ESRI), 2022)
A universal basic income (UBI) is defined as a universal, unconditional cash payment that is made regularly, is sufficient to live on, is not means tested, carries no work requirements and is paid on an individual basis. This study examines the international evidence on universal basic incomes and identifies key issues for consideration in the design of any UBI pilot for Ireland. Despite the mainstream interest in UBI as a potential policy tool, relatively little is known about the associated consequences of such policies. Even the definition of a UBI appears to be poorly understood and is often misused in the public discourse. Several pilot studies have been recently implemented across different countries. However, some pilot studies depart from the accepted definition of UBI. For example, some are not universal, in that they only target a specific subgroup of the population and/or have eligibility restrictions based on earnings. Others provide a relatively low level of payment, which may fall short of what an individual could reasonably be expected to live on. In this study, we undertake some basic calculations relating to four possible UBI approaches, all of which would involve an unconditional payment to every individual aged over 18 in Ireland.
Keywords: 330; Grundeinkommen; Wirkungsanalyse; Kosten; Irland